The Use of biofloors in great ape zoo exhibits - Jesse G. Leinwand; Jill A. Moyse; Lydia M. Hopper; Maureen Leahy; Ross, Stephen R (Journal of Zoo and Aquarium Research, 2021)
The past several decades have seen significant progress in zoo exhibit design, with naturalistic spaces replacing many of the traditional concrete enclosures. Furthermore, research studying the impact of such exhibit design in terms of animal welfare and zoo visitor experience has increased. While this has been especially true for studies of zoo-housed great apes, the effect of the floor type that apes reside on—whether concrete or a softer/organic substrate—has received relatively little attention. To better understand zoos’ motivations for, and experiences with, different flooring substrates, a survey was administered to all 89 zoos accredited by the Association of Zoos and Aquariums that house great apes. Here, the results of the survey are presented and interpreted in the context of the knowledge gained from the four biofloor exhibits housing chimpanzees and gorillas at the Lincoln Park Zoo in Chicago, USA. Of the 62 zoos that responded, 45 reported having indoor exhibit spaces in which visitors could view great apes, but only 13 had exhibits that provide a biofloor as the exhibit substrate. Zoos indicated that animal welfare was a key motivator for installing biofloors, while facility constraints were most often cited as the primary impediment to having a biofloor. Pest control and cleaning protocols only varied slightly across institutions and floor types, with many zoos following similar maintenance procedures. Overall, survey responses and experiences at Lincoln Park Zoo suggest biofloors promote positive welfare without compromising husbandry efforts and are a worthwhile investment.